THE INFLUENCE OF LEADERSHIP STYLE AND GROUP INTEGRATION ON WORK MOTIVATION (Research on Employees at the Gorontalo City-District Office) - Badu, Syamsu Qamar; Djapri , Noviyanty (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
This research aims to see the influence of leadership style and group cohesiveness on employee work motivation, with the hypothesis "there is a positive influence of leadership style and group cohesiveness on work motivation". The research method used is a causal survey method with multiple regression analysis techniques.The research target population was all district and city government employees in Gorontalo Province. Meanwhile, the affordable population is employees of the Gorontalo Regency and Gorontalo City technical services. From this population, 60 employees were selected as research samples. Based on the data analysis that has been carried out, this research produces findings which are concluded as follows: (i) leadership style and group cohesion together have a significant effect on work motivation; (ii) leadership style alone (partially) has a significant effect on work motivation; (iii) group integration alone (partially) has a significant effect on work motivation.